Forme, significati e valori della partecipazione politica giovanile nell'Empolese Valdelsa - Felaco, Cristiano (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
The relationship of the young people with the politics has changed in the postmodern society. The most recent surveys shows that the young prefer individualistic kinds of participation and participate mostly in cultural and social associations. This article aims to analyze the participation of the young members of the “Arci” club in “Empolese Valdelsa” in Tuscany, an area with a long political tradition. In particular, the research attempts to identify the transformation of the values belonging to local political subculture that it has oriented the political life of the people over the years.